The third-wave of cognitive-behavioral therapies for borderline personality disorder in Iran: a systematic review - Fateme Moeeni; Behnaz Dowran; Parviz Dabaghi (فصلنامه ابن سینا)
Background: Among personality disorders, borderline personality disorder is one of the severe and serious psychiatric disorders, and one of the most effective psychological treatments to improve its symptoms is third-wave psychotherapies. The purpose of this study was to perform a systematic review focused on the effect of third wave psychotherapies on borderline personality disorder. Materials and methods: In this systematic review, a search of clinical trials articles was done in Persian and English using the keywords "Borderline Personality Disorder", "Dialectical Behavior Therapy", "Acceptance and Commitment Therapy " and "Schema Therapy". Results: Totally, twelve full-text articles were reviewed. After searching, screening, and evaluation, the results showed that all studies in general (overall score) had reported a positive effect of third wave interventions on improving borderline personality disorder, yet there were differences in some symptoms (such as anger, paranoid beliefs, absurdity, interpersonal relationships, impulsivity, etc.). The findings also showed that this therapy was effective for specific groups, including addicts and prisoners, but such usefulness was different in each group. Conclusion: In summary, studies were conducted on different individuals, small sample size, and different cultural contexts. According to these findings, the third-wave therapeutic interventions were effective in improving symptoms of borderline personality disorder. Further studies, however, are required in order to investigating its effects on some symptoms.